2020
DOI: 10.1590/0034-7167-2019-0406
|View full text |Cite
|
Sign up to set email alerts
|

Access of the patient to the cancer network under the “Sixty-Day Law”: Integrative Review

Abstract: Objectives: to analyze Brazilian scientific production on patient access to the oncology network under the “Sixty-Day Law”. Methods: integrative review of the literature in the databases Lilacs, PubMed and Scielo. The descriptors used were: neoplasms, health services accessibility, early detection of cancer. Articles published from 2015 to March 2019 were included. Results: 17 articles were analyzed and four themes emerged: inequality in access; qualification of Primary Care professionals; time as a determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(106 reference statements)
1
4
0
2
Order By: Relevance
“…However, Primary Health Care (PHC) plays a fundamental role in health promotion, focusing on cancer protection factors, disease screening, early diagnosis, regulation of patients for other levels of care and training of teams, in addition to coordinating and maintaining the care of users with cancer ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Primary Health Care (PHC) plays a fundamental role in health promotion, focusing on cancer protection factors, disease screening, early diagnosis, regulation of patients for other levels of care and training of teams, in addition to coordinating and maintaining the care of users with cancer ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is observed that there are difficulties in providing care to cancer patients in PHC services, due to the need for qualification of professionals involved in the process of identifying signs and symptoms, referral to early diagnosis and treatment, users’ unequal access to available services and delays in carrying out tests and returning for consultations ( 29 ) . Thus, it is necessary to improve actions at this level of health care, to minimize the delay in diagnosis, in the provision of care and in the use of resources, in order to guarantee comprehensive care for patients with hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, a Atenção Primária à Saúde (APS) tem papel fundamental na promoção da saúde com foco nos fatores de proteção relativos ao câncer, na realização de rastreamento da doença, diagnóstico precoce, regulação dos pacientes para outros níveis de atenção e capacitação das equipes, além de coordenar e manter o cuidado dos usuários com câncer (29) .…”
Section: Modelo De Atendimento Compartilhadounclassified
“…Contudo, observa-se que existem dificuldades na prestação da assistência ao paciente com câncer nos serviços de APS, devido à necessidade de qualificação de profissionais envolvidos no processo de identificação de sinais e sintomas, ao encaminhamento ao diagnóstico e tratamento precoce, à desigualdade de acesso dos usuários aos serviços disponíveis e às demoras na realização de exames e retorno para consultas (29) . Assim, faz-se necessário melhorar as ações nesse nível de atenção à saúde, para minimizar o atraso no diagnóstico, na realização dos cuidados e na utilização de recursos, de modo a garantir uma assistência integral ao paciente com neoplasias hematológicas.…”
Section: Modelo De Atendimento Compartilhadounclassified